The justice and policy implications of clean energy transition in Africa - Nsafon, Benyoh Emmanuel Kigha; Same, Noel Ngando; Yakub, Abdulfatai Olatunji; Chaulagain, Deepak; Kumar, Nallapaneni Manoj; Huh, Jeung-Soo (Frontiers in Environmental Science, 2023)
Despite the low local energy access rates, Africa is considered a key player in the global energy transition due to its large supply of fossil fuels and a large reserve of critical minerals essential for manufacturing renewable energy components in the energy sector and storage devices in the transportation and electronics sectors. But building a sustainable society at all levels across nations would only come when there exists a just and inclusive energy transition based on the idea of “leave no one behind”. While many African countries have embarked on ambitious and transformative transition strategies, and many energy projects classified as “clean” have economic, environmental, and social implications that jeopardize the well-being of those already vulnerable to the impacts of climate change. This paper explores the policy implications of the just transition to ensure that efforts to steer Africa towards a lower carbon future are supported by fair, equity, and justice considerations. Our analyses provide valuable evidence for considering a just transition in Africa that will not exacerbate the current socio-economic challenges the region is facing but will support sustained poverty reduction and the achievement of faster economic growth. Our findings show that the African continent's multiple challenges of energy security, economic growth, and affordable access must feature in its clean energy transition. We draw conclusions that an incremental transition emphasizing low-carbon development is the most feasible and pragmatic approach to transform the region’s economy and address climate change challenges.